A contribution to the thermal effects of DLC coatings on fluid friction in EHL contacts. (3rd August 2018) - Bobzin, K.; Brögelmann, T.; Kalscheuer, C.; Thiex, M.; Ebner, M.; Lohner, T.; Stahl, K.
Abstract: Diamond‐like carbon (DLC) coatings are commonly used to reduce boundary and mixed friction in tribological contacts. Recent works at the FZG efficiency gear test rig show that the application of the DLC coating ZrCg (a‐C:H:Zr) on gear flanks reduces the mean coefficient of friction in fluid film lubrication regime by up to 39% compared with uncoated gear flanks. A common explanation is the lower heat dissipation of DLC coatings resulting in higher EHL contact temperatures, hence in lower effective lubricant viscosity in the EHL contact. To gain a deeper understanding, discrete Zrx C1−x coatings were deposited on AISI 5115 using physical vapour deposition technology and thermophysical properties were directly measured. The tribological behavior of the coatings was investigated at the FZG twin‐disc test rig by using mineral gear oil. The results clearly prove the strong influence of the thermophysical properties of the DLC coatings on fluid friction in highly loaded EHL contacts.